Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4251/wjgo.v14.i1.230
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset colorectal cancer: Current insights and future directions

Abstract: Early-onset colorectal cancer (EOCRC) has seen an alarming rise worldwide over the past two decades. The reason for this global trend is poorly understood. EOCRC appears to have its own unique clinical and molecular features when compared with late-onset colorectal cancer. Younger patients appear to have more distal or rectal disease, a more advanced stage of disease at presentation, and more unfavorable histological features. Identifying risk factors for EOCRC is the first step in mitigating the rising burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 87 publications
0
21
0
1
Order By: Relevance
“…A number of studies have implicated generational shifts in lifestyle factors as important contributors to the rise of EOCRC within Western populations [ 10 ]. We have previously shown that exposure of normal colon organoids to several different CRC related lifestyle factors led to widespread gene expression differences that are enriched for genes associated with CRC [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have implicated generational shifts in lifestyle factors as important contributors to the rise of EOCRC within Western populations [ 10 ]. We have previously shown that exposure of normal colon organoids to several different CRC related lifestyle factors led to widespread gene expression differences that are enriched for genes associated with CRC [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the strong enrichment of the FAP DEGs observed here and CRC, we were not surprised to see that FAP DEGs were also enriched for targets of various CRC lifestyle factors. Importantly, one theory attempting to explain the rise in EOCRC rates observed across recent generations centers on changes in Western lifestyle, including increased alcohol consumption [ 10 ]. As such, we performed qPCR analysis on a subset of genes previously found to be altered following ethanol treatment that were also differentially expressed in FAP colon organoids and in at least one EOCRC dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRC occurrence and development are caused by complex biological processes, including gene mutation, imbalance of cell proliferation, differentiation and apoptosis. [ 27 ]. Therefore, further searching for high-sensitivity, high-specificity, and high-stability diagnostic markers and possible targets for clinical treatment is particularly important for the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in APC, MMR genes, and MUTYH are known drivers of hereditary CRC syndromes and are represented in EOCRC patients. 75 However, there are also non–colorectal-related germline mutations that predispose to EOCRC, including variants in BRCA1, BRCA2, TP53, and EGFR. 64 Up to 29% of EOCRC tumors are MSI-H, compared with 15% of all CRC, and this accounts for patients with and without Lynch syndrome.…”
Section: Early-onset Colorectal Cancermentioning
confidence: 99%